IGF-1 activates a Cilium-localized noncanonical Gβγ signaling pathway that regulates cell-cycle progression - Yeh, Celine (2013)
Primary cilia undergo cell-cycle-dependent assembly and disassembly. Emerging data suggest that ciliary resorption is a checkpoint for S phase reentry and that the activation of phospho(T94)Tctex-1 couples these two events. However, the environmental cues and molecular mechanisms that trigger these processes remain unknown. Here, we show that insulin-like growth-1 (IGF-1) accelerates G1-S progression by causing cilia to resorb. The mitogenic signals of IGF-1 are predominantly transduced through IGF-1 receptor (IGF-1R) on the cilia of fibroblasts and epithelial cells. At the base of the cilium, phosphorylated IGF-1R activates an AGS3-regulated Gβγ signaling pathway that subsequently recruits phospho(T94)Tctex-1 to the transition zone. Perturbing any component of this pathway in cortical progenitors induces premature neuronal differentiation at the expense of proliferation. These data suggest that during corticogenesis, a cilium-transduced, noncanonical IGF-1R-Gβγ-phospho(T94)Tctex-1 signaling pathway promotes the proliferation of neural progenitors through modulation of ciliary resorption and G1 length.